2015
DOI: 10.1007/s12665-015-4759-y
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of cross-country transport in raster format

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer-Verlag Berlin Heidelberg. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 7 publications
(5 reference statements)
0
25
0
1
Order By: Relevance
“…The same approach in which terrain trafficability studies were carried out entirely with remote sensing data was presented by Bacon et al (2008), Kruse et al (2000), and Sadiya et al (2017). Campbell (2012), Dawkins (2011), Gustafsson and Hägerstrand (2005), Kirkland (1981), Kristalova (2015), Mohamad Rabab (2002), Mohtashami et al (2012) and Rybansky et al (2015) used high resolution satellite images and Light Detection and Ranging (LIDAR) recordings in order to implement high accuracy and precision data in their research, which gave DMR and vegetation cover data greater accuracy (Andersen et al, 2003). It should be emphasised that remote sensing data analysis cannot achieve complete detail and reliability in terms of data (Leighty, 1965;Kruse et al, 2000;Wawer et al, 2003), and vegetation and soil data cannot be collected without direct verification in the field (Laskey et al, 2010).…”
Section: Physicalgeographic Factors Of Terrain Trafficability Of Milimentioning
confidence: 99%
See 2 more Smart Citations
“…The same approach in which terrain trafficability studies were carried out entirely with remote sensing data was presented by Bacon et al (2008), Kruse et al (2000), and Sadiya et al (2017). Campbell (2012), Dawkins (2011), Gustafsson and Hägerstrand (2005), Kirkland (1981), Kristalova (2015), Mohamad Rabab (2002), Mohtashami et al (2012) and Rybansky et al (2015) used high resolution satellite images and Light Detection and Ranging (LIDAR) recordings in order to implement high accuracy and precision data in their research, which gave DMR and vegetation cover data greater accuracy (Andersen et al, 2003). It should be emphasised that remote sensing data analysis cannot achieve complete detail and reliability in terms of data (Leighty, 1965;Kruse et al, 2000;Wawer et al, 2003), and vegetation and soil data cannot be collected without direct verification in the field (Laskey et al, 2010).…”
Section: Physicalgeographic Factors Of Terrain Trafficability Of Milimentioning
confidence: 99%
“…Nakon izrađenoga modela i provedenih računalnih kalkulacija neki su autori proveli i empirijska istraživanja točnosti modela na samom terenu u stvarnim situacijama (Hohmann i dr., 2013), a to je ujedno i al. (1992), Li et al (2007), Murphy and Randolph (1994), Rybansky et al (2015) and Talhofer et al (2015) have all tested their models on the ground using GPS receivers. The authors have used results implemented using the NRMM model as the most frequent and most commonly applied parameters in calculations within their models.…”
Section: Physicalgeographic Factors Of Terrain Trafficability Of Milimentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency relief in large-scale earthquake disasters is a complicated system involving many components. The dynamic constraints affecting EMVDR lie in the emergency materials and transportation network [21,22]. Firstly, the emergency material supplies come from the government supply repositories, purchase, donation, production, and so on.…”
mentioning
confidence: 99%
“…Agent-based models are normally utilized as effective methods of simulating human behavior in certain environment such as in emergencies (e.g., Vanclooster et al 2014). Focusing on movement, in this issue, Rybansky et al (2015) found that modeling the movement of vehicles in open terrain is more difficult because many factors affect vehicle deceleration, including terrain surface configuration, surface roughness, and materials, as well as obstacles in the route. To deliver a proper solution, he designed a method for calculating vehicle deceleration that synthesized corresponding raster cells in an elementary terrain area with influences from geographic factors.…”
mentioning
confidence: 99%